2016
DOI: 10.1016/j.jaci.2015.10.050
|View full text |Cite
|
Sign up to set email alerts
|

Impaired barrier function in patients with house dust mite–induced allergic rhinitis is accompanied by decreased occludin and zonula occludens-1 expression

Abstract: We found impaired nasal epithelial barrier function in patients with HDM-induced AR, with lower occludin and zonula occludens-1 expression. IL-4 disrupted epithelial integrity in vitro, and FP restored barrier function. Better understanding of nasal barrier regulation might lead to a better understanding and treatment of AR.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
327
0
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 281 publications
(342 citation statements)
references
References 46 publications
11
327
0
4
Order By: Relevance
“…Early studies by Davies, Holgate, Hackett, Knight and others found evidence for persistence of EMT in asthma 120123 , although it is more often described as a mild, “partial EMT” phenotype, which could contribute to poor expression of conventional EMT markers in asthmatic airways 32 . More recent studies found similar evidence for increased EMT in allergic rhinitis 42, 43 . Several studies have demonstrated ongoing EMT in CRS 37, 47, 4951 .…”
Section: Mechanisms Of Barrier Defectssupporting
confidence: 55%
See 1 more Smart Citation
“…Early studies by Davies, Holgate, Hackett, Knight and others found evidence for persistence of EMT in asthma 120123 , although it is more often described as a mild, “partial EMT” phenotype, which could contribute to poor expression of conventional EMT markers in asthmatic airways 32 . More recent studies found similar evidence for increased EMT in allergic rhinitis 42, 43 . Several studies have demonstrated ongoing EMT in CRS 37, 47, 4951 .…”
Section: Mechanisms Of Barrier Defectssupporting
confidence: 55%
“…In vitro , IL-4 and TNF induced loss of these markers in epithelium. Steelant et al observed decreased barrier function measured in vitro using primary epithelial cells collected in patients with allergic rhinitis compared to healthy controls and found decreased expression of the tight junction proteins occludin and ZO-1 43 .…”
Section: Barrier Defects In Type 2 Diseasesmentioning
confidence: 99%
“…Lee et al reported decreased ZO-1 and E-cadherin expression in the nasal epithelium of patients with AR 20 . Consistent with these findings, Steelant et al reported decreased ZO-1 and occludin expression as assessed by RT-qPCR and weak immunofluorescent staining in AR biopsy specimens 21 .…”
Section: Epithelial Barrier Function In Atopic Diseasesupporting
confidence: 52%
“…Steelant et al have also investigated the functional consequences of barrier dysfunction in symptomatic AR 21 . To do so, they first obtained nasal biopsy specimens from control and house-dust mite (HDM)-AR patients.…”
Section: Epithelial Barrier Function In Atopic Diseasementioning
confidence: 99%
“…It not only largely affects social life, sleep and work, but also increases family and socioeconomic burden [1]. Despite rapid progress in the treatment of AR, such as immunotherapy, intranasal steroids, and antihistamines, 20% of AR patients already do not show sufficient subjective and objective improvement [3]. Accordingly, it is of foremost importance to develop potential pharmacological agents for the treatment of AR.…”
Section: Introductionmentioning
confidence: 99%